The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology